Ideas para el socialismo del futuro / Miguel Ángel Quintanilla, Ramón Vargas-Machuca - Vargas-Machuca Ortega, Ramón; Quintanilla, Miguel Ángel
Separata de: Leviatán : revista de hechos e ideas, n° 18, invierno 1984 (II época), p. 96-104